Effect of chromogranin A N-terminal fragment vasostatin-1 nano-carrier transfection on abdominal aortic aneurysm formation - Pingshan Wang (Taylor & Francis Group, 2021)
The effects of transfection of N-terminal fragment of chromogranin A Vasostatin-1 (VS-1) nanocarriers on formation of abdominal aortic aneurysm (AAA) were discussed, and its mechanism was analyzed. Nanoparticles containing VS-1 genes were prepared by emulsion solvent evaporation method, and property of nanoparticles was examined. A total of 30 male SD rats were divided randomly into sham group (normal saline), AAA group (Type I porcine pancreatic elastase), and VS-1 group (Type I porcine pancreatic elastase+VS-1 suspension liquid). The diameter dilation of rats was measured, abdominal aortic morphology was observed by HE staining, and levels of AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) were examined by immunohistochemistry and Western blot. Correlation between AMPK as well as mTOR and diameter dilation was analyzed by Pearson correlation. VS-1 genes in VS-1 nanoparticles were 4.51% and coating efficiency of genes was 88%. Compared with rats in sham group, diameter dilation of rats in AAA group increased, damage of abdominal aorta in rats was obvious, p-AMPK decreased, and p-mTOR increased in AAA group. Compared with AAA group, diameter dilation of rats in VS-1 group decreased, abdominal aorta of rats was improved, p-AMPK increased, and p-mTOR decreased. The comparison of all above indicators had statistical meaning (P < 0.05). p-AMPK and p-mTOR were negatively (r = −0.9150 and P = 0.006) and positively correlated with the diameter dilation (r = −0.9206 and P = 0.001). VS-1 nanoparticles could inhibit the formation of AAA, which might be related to the activation of AMPK/mTOR signal path.